Aplikasi Alat Bantu Mesin Bubut untuk Pengerjaan Spinning - Mohd Ridwan; Seno Darmanto; Benidiktus Tulung Prayoga; Syamsul Hadi (Sekolah Vokasi Universitas Diponegoro, 2025)
The potential, opportunities, and advantages of Banaran Village, Cepogo District, Boyolali should serve as capital and driving force in driving a people's economy based on local wisdom and national orientation. In addition to promoting the metal carving industry sector, other potentials and advantages of Banaran Village, Cepogo, Boyolali include highland agriculture, historical heritage, arts and culture, natural scenery, reservoirs/reservoirs, and service potential. The solutions implemented in this activity are principally based on the potential and constraints faced by partners, especially Tumang Village, Banaran, Cepogo District, Boyolali. The relatively large and labor-intensive potential of small and medium industries in Tumang will be encouraged to open themselves to the potential of the accompanying economy in addition to the main sector, namely copper carving products and the like, by implementing lathe-based spinning machines covering education, arts and culture, tourism, agriculture, and other superior economic products. In addition, these potentials, opportunities, and advantages will be encouraged with good management and governance patterns so that community movements can also stimulate the economic movements of the surrounding community